Avaliação da ação espasmolítica do flavonoide 3,6-Dimetil éter galetina, isolado de Piptadenia stipulacea (Benth.) Ducke e investigação do mecanismo de ação em traqueia de cobaia e aorta de rato - Macêdo, Cibério Landim (2012)
The flavonoid galetin 3,6 dimethyl ether (FGAL) was isolated from the aerial parts of Piptadenia stipulacea (Benth.) Ducke and was investigated its possible hemolytic activity in rat erythrocytes and spasmolytic activity in several isolated smooth muscles as rat uterus, guinea pig ileum and trachea, and rat aorta. FGAL showed no hemolytic effect on rat erythrocytes, which is suggestive of a low toxicity. In preliminary pharmacological screening performed in smooth muscle models, FGAL showed non-selective spasmolytic effect in the four organs tested, with a higher potency to relax the guinea pig trachea pre-contracted with carbachol and rat aorta pre-contracted with phenylephrine (FEN) in a functional epithelium and endothelium independent manner, respectively. The aim of this study was to investigate the action mechanism of FGAL relaxing effect in guinea pig trachea and rat aorta. The observation that FGAL was more potent in relaxing both pre-contracted organs with moderate increases in extracellular concentration of KCl than when contracted with larger increases of KCl is suggestive that FGAL modulates the channels positivety. This hypothesis was confirmed by decreasing of relaxant potency of FGAL in both organs in the presence of tetraethylammonium (TEA+) 10 mM, non-selective blocker of K+ channels. To determine the subtypes of K+ channel involved, were used selectives blockers: in trachea the effect of FGAL was not altered in the presence of TEA+ 1 mM, blocker of large conductance calcium-activated K+ channels (BKCa); glibenclamide, blocker of sensitive-ATP K+ channels (KATP); BaCl2, blocker of inward rectifier K+ channels (Kir) or 4-AP, blocker of voltage activated K+ channels (KV), but was reduced in the presence of apamin, blocker of small conductance calcium-activated K+ channels (SKCa). In aorta, the relaxant effect of FGAL was not altered in the presence of TEA+ 1 mM, but was reduced in the presence of apamin, glibenclamide, BaCl2 and 4-AP, suggesting the involvement of SKCa, KATP, Kir and KV in vasorelaxant action of flavonoid. The fact of FGAL rightward shifted, with Emax reduced the CaCl2-induced contractions in depolarizing medium, and CaCl2 in the presence of verapamil, a voltage activated calcium channel (CaV) blocker, and FEN, suggests the involvement of CaV and ROCs (receptor-operated calcium channel), respectively. Also in the aorta, FGAL inhibited FEN induced contractions in Ca2+-free medium, suggesting inhibition of Ca2+ release from the sarcoplasmic reticulum SR. We also evaluated the participation of the cyclic nucleotides pathway, and observed that the trachea and aorta relaxation induced by aminophylline, non selective inhibitor of phosphodiesterases (PDEs), was more potent in the presence of FGAL, suggesting the involvement of cAMP and/or cGMP. On the aorta was assessed FGAL effect on relaxation induced by selective inhibitors of PDE-3 (milrinone, cAMP selective) and PDE-5 (sildenafil, cGMP selective), and FGAL only potentiated the relaxation induced by sildenafil, suggesting the participation of cGMP. Since K+ channels are modulated negatively by PKC, we investigated a possible inhibition of PKC by FGAL and the flavonoid relaxed the aorta pre-contracted with a PKC activator (PMA), suggesting inhibition of this enzyme. In conclusion, the spasmolytic mechanism of FGAL in trachea involves positive modulation of SKCa and cyclic nucleotides, and in the aorta involves the positive modulation of KATP, SKCa, Kir, Kv and inhibition of CaV, ROCs, Ca2+ release of SR, PDE-5 and PKC.